The Influence of Price and Service Quality on Customer Satisfaction Adidas Store Living World Alam Sutera - Julya Latifah; Fahrul Mumtaz; Jaka Hariyadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research was conducted with the aim to determine the effect of price, service quality on customer satisfaction Adidas Store Living World Alam Sutera. This study uses primary data sourced from 118 respondents. Data were analyzed using multiple linear regression equations, coefficient of determination (R2), t test and F test. The results showed that the results of the test for the coefficient of determination (R2) obtained Ajusted R Square of 42.3% product, promotion and price variables had an influence on the decision to buy a house at Green Avina in Birem Puntong Langsa Baro and the remaining 57.7% is influenced by other variables not included in this study such as location and facilities. The results of the t test show that partially the product, price and promotion variables have a significant effect on the decision to buy a house at Green Avina Birem Puntong Langsa Baro. The results of the F test show that simultaneously the product, price and promotion variables have a significant effect on home buying decisions at Green Avina Birem Puntong Langsa Baro.